PERSEPSI MASYARAKAT TERHADAP KEBERADAAN RUMAH POTONG HEWAN (RPH) DI KOTA BLITAR - Esa Cahya Putra; Alfan Setya Winurdana; Edya Moelia Moeis (Journal of Livestock Science and Production, 2024)
This research aims was to determine the perception about response of community the existence of a Slaughterhouse (RPH) in Blitar City. This research uses two variables positive perceptions and negative perceptions. The positive perception variable has 3 sub-variables: job vacancies, ease of slaughtering slaughter services, and social social assistance. Negative perception variable has 4 sub-variables: water and air pollution (odor), flies, causing noise and health problems. Sampling was carried out using a purposive sampling method, where the sample from this research was the entire community of RT 02 RW 01 Sukorejo Village, totaling 85 heads of families. The data analysis used in this research is descriptive statistics using grouping, simplification and presentation of data such as frequency distribution tables and measurements using a Likert scale. The results of the research show that the positive perception score for the surrounding community is 142, while the negative perception score for the surrounding community is 164. These results indicate that these two variables have a negative or positive perception of the existence of the Slaughterhouse (RPH).